2014
DOI: 10.1097/mbc.0b013e328364a802
|View full text |Cite
|
Sign up to set email alerts
|

Antibody binding, platelet adhesion, and protein adsorption on various polymer surfaces

Abstract: Commercially available polymer surfaces for in vitro applications are characterized to different extents in terms of hydrophobicity, binding preferences, and immunoglobulin capacity. We compared five, well or poorly defined polystyrene plates, used as standard hydrophobic surfaces for studying biological interactions. Antibody binding (ELISA) and platelet adhesion (release of alkaline phosphatase from adhered platelets) were contrasted with total protein adsorption (alkaline phosphatase assay and bicinchoninic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 22 publications
0
11
0
2
Order By: Relevance
“…In addition to using diluted protein solutions for mechanistic studies, it is particularly interesting to apply application‐relevant concentrations, e.g., physiological concentrations, for predictive studies of competition and exchange. For example, at cell culture plates with different proposed binding capabilities, fibronectin only showed differences in adsorption at low protein concentrations, but these differences were insignificant at higher concentrations 111. While the supernatant of polymer samples with the nonadsorbed protein fraction is easily accessible, higher precision may be assigned to a characterization of the adsorbed protein fraction.…”
Section: Methods For the Analysis Of Protein Interactionsmentioning
confidence: 98%
See 1 more Smart Citation
“…In addition to using diluted protein solutions for mechanistic studies, it is particularly interesting to apply application‐relevant concentrations, e.g., physiological concentrations, for predictive studies of competition and exchange. For example, at cell culture plates with different proposed binding capabilities, fibronectin only showed differences in adsorption at low protein concentrations, but these differences were insignificant at higher concentrations 111. While the supernatant of polymer samples with the nonadsorbed protein fraction is easily accessible, higher precision may be assigned to a characterization of the adsorbed protein fraction.…”
Section: Methods For the Analysis Of Protein Interactionsmentioning
confidence: 98%
“…by gel chromatography), their direct selective biochemical detection (e.g. with antibodies,111 aptamers124, 125), or indirect detection (after labeling) 126128…”
Section: Methods For the Analysis Of Protein Interactionsmentioning
confidence: 99%
“…So that the ADC sprayed on the stent can solve a series of side effects of hemolysis, coagulation and inflammation response which caused by plasma protein and platelet adhesion and aggregation on the stent after stent implantation 28 . We also found that the ADC could significantly prolong the APTT, PT and TT and reduce the amount of Fbg adsorption compare with other groups, which indicating that SZ-21 can slow down the clotting system of endogenous and exogenous system, and some studies have shown that Fbg adhesion reduction also inhibits thrombosis [29][30][31] , so the ADC have good blood compatibility. Moreover, the hemolysis rate of ADC was less than 5 % which meet the standards that clinical use of biological material requires 32 .…”
Section: Discussionmentioning
confidence: 66%
“…Es konnte z. B. an Zellkulturplatten mit verschiedenen bereitgestellten Bindungskapazitäten gezeigt werden, dass Fibronektin nur bei geringer Konzentration Unterschiede im Adsorptionsverhalten aufweist und dass diese Unterschiede bei höherer Konzentration unbedeutend sind 111. Während der Überstand einer Polymerprobe mit dem Anteil der nicht‐adsorbierten Proteine leicht zugänglich ist, ist eine höhere Genauigkeit bei der Charakterisierung des adsorbierten Polymerteils notwendig.…”
Section: Methoden Für Die Analyse Von Proteinwechselwirkungenunclassified
“…B. durch Gelchromatographie, oder ihren direkten selektiven biochemischen Nachweis, z. B. mithilfe von Antikörpern111 oder Aptameren,124, 125 oder indirekten Nachweis (nach einer Markierung) 126128…”
Section: Methoden Für Die Analyse Von Proteinwechselwirkungenunclassified